Proceedings of the 16th International Conference on Multimodal Interaction 2014
DOI: 10.1145/2663204.2663271
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Respiration for Prediction of "Who Will Be Next Speaker and When?" in Multi-Party Meetings

Abstract: To build a model for predicting the next speaker and the start time of the next utterance in multi-party meetings, we performed a fundamental study of how respiration could be effective for the prediction model. The results of the analysis reveal that a speaker inhales more rapidly and quickly right after the end of a unit of utterance in turn-keeping. The next speaker takes a bigger breath toward speaking in turn-changing than listeners who will not become the next speaker. Based on the results of the analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
40
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 17 publications
0
40
1
Order By: Relevance
“…inhalation duration and inhalation delay. Thus, previous findings of temporal compression in turn-keeping [4,5,17] could be replicated. Contrary to previous findings [17], we have shown that inhalation amplitude and inhalation starting level also make significant contributions to predictions of turn-taking behaviour.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…inhalation duration and inhalation delay. Thus, previous findings of temporal compression in turn-keeping [4,5,17] could be replicated. Contrary to previous findings [17], we have shown that inhalation amplitude and inhalation starting level also make significant contributions to predictions of turn-taking behaviour.…”
Section: Discussionmentioning
confidence: 59%
“…We arrived at these models by hierarchical entry of predictors [16]. We first entered inhalation duration as this was one of the two most robust features in [6], and this improved all three models significantly compared to a model where only the constant was included. We entered inhalation amplitude next, and this also improved all models significantly.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, however, there has been little work on whether breathing sounds are used as cues to turnmanagement. Admittedly, several authors, including the present ones, have suggested that breathing is a turn-taking cue [20,21,22,23,24], however the evidence was based on breathing kinematics measured with elastic belts wrapped around speakers' thorax. While this method delivers a gold standard in the detection of respiratory events [12], it is relatively invasive and difficult to incorporate into a spoken dialogue system, not least because it requires a relatively time-consuming calibration procedure.…”
Section: Introductionmentioning
confidence: 82%
“…One important requirement for a fluent and successful conversation is an efficient turn-taking, which has to be organized by specific "underlying mechanisms", such as intonation, semantic cues, facial expressions, eye contact, breathing, and gestures [2], [3], [4]. In the organization of turn-taking and to evaluate the conversation, overlapping speech has a major role.…”
Section: Introductionmentioning
confidence: 99%